144k views
4 votes
(2x? – 6x² +8x) = (2x+2)

1 Answer

6 votes

In case, it is 2x-6x²+8x, Isolating all terms on the left side:

1) (2x-6x²+8x) =(2x +2)

2x-6x²+8x -2x -2 =0

-6x²+8x -2 =0

6x² -8x -2 =0


\begin{gathered} x=\frac{8\pm\sqrt[]{64-4(6)(-2)}}{12} \\ \\ x_1=\frac{2+\sqrt[]{7}}{3} \\ x_2=\frac{2-\sqrt[]{7}}{3}_{} \end{gathered}

2) In case, it is 2x²-6x²+8x. Isolating all terms on the left side.

2x²-6x²+8x =2x +2

-4x²+8x-2x -2=0

-4x² +6x -2 =0

4x²-6x+2=0


\begin{gathered} x=\frac{6\pm\sqrt[]{(36)-4(4)(2)}}{8} \\ \\ x_1=1 \\ \\ x_2=(1)/(2) \end{gathered}

User Fedalto
by
6.8k points